THE CONTRIBUTION OF KH. MUHAJIRIN AMSARI AD-DARY IN THE DEVELOPMENT OF ISLAMIC EDUCATION AND DA'WAH IN INDONESIA - Anim, Sarbini; Uyuni, Badrah; Majid, Zamaksyari Abdul; Fahrany, Sofia; Adnan, Mohammad (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: Islamic scholars have historically played a vital role in shaping Jakarta’s Islamic landscape, actively contributing to the spread of Islam through education, da'wah, and the establishment of religious organizations. Extending their influence beyond religious matters, these scholars have fostered economic empowerment, cultural preservation, and unity among Muslims in the region. Purpose: This study delves into the contributions of KH. Muhajirin Amsari Ad-Dary, is a distinguished religious figure within the Betawi community, highlighting his pivotal role in advancing Islamic knowledge, da'wah, and social cohesion. Through his scholarly works, da'wah efforts, and community leadership, KH. Muhajirin Amsari Ad-Dary significantly impacted the religious practices, education, and spiritual development of the Betawinese. Method: This research examines his methods and influence, showcasing how he shaped the religious identity and unity of the Betawi community while preserving their Islamic and cultural heritage. Result: By focusing on his legacy in Islamic scholarship and community leadership, this study underscores the enduring influence of Betawi ulama in sustaining religious and cultural identity, positioning KH. Muhajirin Amsari Ad-Dary's contributions are emblematic of the broader impact of Betawi scholars on the development of Islam in Jakarta. Conclusion: KH. Muhajirin Amsari Ad-Dary's contributions exemplify the vital role of Betawi scholars in enriching Islamic education, promoting community unity, and preserving cultural heritage in Jakarta.